Determinants of Women - Ilmiyah, Desy Eka; Budihastuti, Uki Retno; Nurhaeni, Ismi Dwi Astuti; Mudigdo, Ambar (Journal of Maternal and Child Health, 2018)
Background: Long-acting reversible contraceptives (LARCs) are the most effective methods of birth control. LARCs include the copper IUD, the hormonal (progesterone) IUD, and the